Vijand in beeld - Buyse, Axel; de Temmerman, Els; D'Hondt, Paula; Simons, Marie-Jeanne; Vandepitte, Paul; Vanbeselaere, Norbert (Antwerpen: Pax Christi Vlaanderen, 1991)
"Axel Buyse, Els De Temmerman, Paula D'Hondt-Vanopdenbosch... et al."